1991
DOI: 10.7326/0003-4819-115-9-694
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Glucose Control in Patients with Pancreatic Transplants

Abstract: Pancreas transplantation, in our successful cases, lowered glycosylated hemoglobin to normal or near-normal levels that were sustained for as long as 5 years. These results compare favorably with those in our patients on standard treatment, and also with those in similar patients on intensive control reported by others. Further effort to improve transplant methods appears to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 26 publications
0
20
0
2
Order By: Relevance
“…54 The metabolic profile and glucose tolerance test studies were used in era 2 to compare posttransplant endocrine function by duration of pancreas graft preservation 106 and to compare function in recipients who did or did not have reversible rejection episodes. 81 The results were similar regardless of preservation time or occurrence of rejection episodes in recipients with sustained insulin independence; glycosylated hemoglobulin levels, 112 both in the short term 151 and the long term, 114 were normal. Era 2 saw the introduction of more sophisticated metabolic studies using new methods initiated by coauthor R.P.R.…”
Section: Metabolic Studiesmentioning
confidence: 56%
“…54 The metabolic profile and glucose tolerance test studies were used in era 2 to compare posttransplant endocrine function by duration of pancreas graft preservation 106 and to compare function in recipients who did or did not have reversible rejection episodes. 81 The results were similar regardless of preservation time or occurrence of rejection episodes in recipients with sustained insulin independence; glycosylated hemoglobulin levels, 112 both in the short term 151 and the long term, 114 were normal. Era 2 saw the introduction of more sophisticated metabolic studies using new methods initiated by coauthor R.P.R.…”
Section: Metabolic Studiesmentioning
confidence: 56%
“…Several factors associated with successful pancreatic transplantation may help reverse some of the above consequences of IDDM. First, pancreatic transplantation results in normalization of glucose homeostasis and abolition of hyperglycaemia 25 . Second, Cheung et al 6 reported a significant improvement in diabetic microangiopathy after SPK transplantation, including reversal of diameter to normal, an increase in arterial length per area and an improvement in vascular perfusion compared with KTA controls.…”
Section: Discussionmentioning
confidence: 99%
“…Either a limitation in the growth capacity oftransplanted islets compared to endogenous pancreatic islets, or an increased death rate overwhelming the growth capacity could lead to continuous loss of beta cell mass and failure ofthe graft. Such factors could help explain the discrepancies between the long-term success of whole pancreas transplantation and the limited survival of islet transplantations in large animals and in humans (3,10,15). However, little is known about the growth capacity and fate oftransplanted beta cells and the factors that modify such events.…”
Section: Introductionmentioning
confidence: 99%